Crosstalk between neuroendocrinology and follicular dynamism: the mare experimental model for reproductive “aging” in women - Esterina Fazio (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche)
The study of reproductive physiology in relation to advancing age is of great interest and involves many species, evaluating the mare as a potential model to study follicular and oocyte maturation in the woman. As in women, the mare has a comparable timing with the events associated with follicular and oocyte maturation, having a long follicular phase, a large follicle size, and the timing between human chorionic gonadotrophin (hCG) o equine chorionic gonadotrophin (eCG) administration and ovulation nearly superimposable. Follicular dynamism is characterised by three functional moments whose endocrine mechanisms dictate their physiological sequence of events: Recruitment, selection and dominance. Aging had caused profound functional alterations at the ovarian level, counaltered luteal phase, LH and progesterone, reduced follicular phase, compensated by increased FSH and E2, increased cycle duration and inter-ovulatory intervals, intermittent ovulations, and increased pool of growing primordial follicles, resulting in accelerated depletion of ovarian reserve.